Oil extraction and deforestation: A simulation exercise - Diego Azqueta; Gonzalo Delacámara (CEPAL Review, 2008)
Existing oil fields in Ecuador are approaching the end of their economic life, and permits to exploit new fields in the Amazon region are being granted. The possibility that deforestation may occur in some areas of high ecological value, as has happened in the past as a result of induced migration, justifies posing a simple question: would it be reasonable to exploit these new fields without causing deforestation? This paper does not claim to give an exhaustive answer to this question but, based on previous research, presents a simulation exercise in which the economic value of four tropical forest services are introduced, in order to evaluate the economic loss that deforestation would entail. It is further argued that the environmental impact appraisal should take into account the corresponding premium accorded to investment. In addition, the use of a hyperbolic discount factor is recommended.